2010
DOI: 10.1016/j.infbeh.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of infant prehension handedness: A longitudinal analysis during the 6- to 14-month age period

Abstract: Abstract:Handedness is a developmental phenomenon that becomes distinctively identifiable during infancy. Although infant hand-use preferences sometimes have been reported as unstable, other evidence demonstrates that infant hand-use preference for apprehending objects can be reliably assessed during the second half of the infant's first year of life. The current study provides further insight into the stability of prehension preferences. We modeled individual and group level patterns of prehension handedness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 25 publications
(30 reference statements)
9
64
1
Order By: Relevance
“…Third, we wanted to check to what extent infant handedness varies with the number of trials used to measure it, and to find the point from which giving more trials does not change the result. Globally, our results agree with most studies showing a higher percentage of right-than left-handers, but also a high percentage of non-lateralized infants (Cornwell et al, 1991;Ferre et al, 2010;Gesell & Ames, 1947;Hawn & Harris, 1983;Lewkowicz & Turkewitz, 1982;McCormick & Maurer, 1988;Michel et al, 1985;Morange & Bloch, 1996;Provins et al, 1987;Ramsay, 1980). When all 34 trials are considered, the main differences between HIs and between their respective distributions into handedness groups are observed between the formula including bimanual grasps (HIf) and the formulae excluding bimanual grasps (HIfwoBim and HIm).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Third, we wanted to check to what extent infant handedness varies with the number of trials used to measure it, and to find the point from which giving more trials does not change the result. Globally, our results agree with most studies showing a higher percentage of right-than left-handers, but also a high percentage of non-lateralized infants (Cornwell et al, 1991;Ferre et al, 2010;Gesell & Ames, 1947;Hawn & Harris, 1983;Lewkowicz & Turkewitz, 1982;McCormick & Maurer, 1988;Michel et al, 1985;Morange & Bloch, 1996;Provins et al, 1987;Ramsay, 1980). When all 34 trials are considered, the main differences between HIs and between their respective distributions into handedness groups are observed between the formula including bimanual grasps (HIf) and the formulae excluding bimanual grasps (HIfwoBim and HIm).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the high frequency of non-lateralized infants, most infant handedness longitudinal and cross-sectional studies, using different methodologies, have in common to show that the percentage of right-hand grasps exceeds that of left-hand grasps as soon as infants start grasping objects successfully (Cornwell, Harris, & Fitzgerald, 1991;Ferre, Babik, & Michel, 2010;Gesell & Ames, 1947;Hawn & Harris, 1983;Lewkowicz & Turkewitz, 1982;McCormick & Maurer, 1988;Michel, Ovrut, & Harkins, 1985;Morange & Bloch, 1996;Provins, Dalziel, & Higginbottom, 1987;Ramsay, 1980). However, the percentage of lateralized versus non-lateralized infants varies from one study to another, as well as the importance of the fluctuations reported for hand preference across sessions (Carlson & Harris, 1985;Corbetta & Thelen, 1999;Fagard, 1998;Michel, 1984;Michel et al, 1985;Michel, Tyler, Ferre, & Sheu, 2006;Ramsay, 1985) (see Table 1).…”
mentioning
confidence: 99%
“…In these ages, infant are still in a refinement process, exploring objects 24 and acquiring experiences in a variety of actions because at 36 months, as expected, they performed predominantly unimanual reaching, independently of the size and rigidity of the objects. At 36 months, it is suggested that infants are able to process the perceptual-motor information and to note that the objects are not sufficiently large in relation to the size of their hands to be bimanual apprehended.…”
Section: Discussionsupporting
confidence: 56%
“…At 5 months of age infants reach equally with the right and left when a toy is presented at midline (Souza, de Azevedo Neto, Tudella, & Teixeira, 2012). From ages 6 to 12 months infants show unstable hand-use preference, meaning they do not show a consistent side of the body for reaching (Ferre, Babik, & Michel, 2010;Lynch, Lee, Bhat, & Galloway, 2008). As such, early stable hand preferences may signal a motor disability.…”
mentioning
confidence: 99%